Lithocarpus polystachyus Rehd. ameliorates cerebral ischemia/reperfusion injury through inhibiting PI3K/AKT/NF-κB pathway and regulating NLRP3-mediated pyroptosis - Liu, Daifang; Wu, Wendan; Wang, Tingting; Zhan, Guiyu; Zhang, Yuandong; Gao, Jianmei; Gong, Qihai (Frontiers in Pharmacology, 2024)
Cerebral ischemia/reperfusion injury (CIRI) exacerbates neuronal damage by enhancing neuroinflammation and oxidative stress. Reactive oxygen species (ROS) can trigger the activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and the NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome, initiating and amplifying inflammatory responses. Thus, the inhibition of the ROS/NF-κB/NLRP3 axis may offer a promising therapeutic approach for CIRI. Sweet tea (ST) comprises several bioactive components, such as phlorizin, trilobatin, and phloretin, with diverse pharmacological activities. However, it remains uncertain whether ST can confer protection against CIRI. In this study, we aimed to investigate the impact and potential underlying mechanism of ST in the context of CIRI. Our results revealed that ST treatment significantly ameliorated brain damage in rats subjected to CIRI by mitigating mitochondrial oxidative stress and neuroinflammation. Additionally, we identified the PI3K/AKT/NF-κB pathway and the NLRP3-mediated pyroptosis axis as crucial processes, with NLRP3 emerging as a primary target in the protective effects of ST. Most intriguingly, molecular docking suggested direct interactions between the main compounds of ST and NLRP3, implying that NLRP3 holds promise as a therapeutic target for ST-induced cerebral protection. In summary, our findings demonstrate that ST safeguards against CIRI-induced neuronal loss, neuroinflammation and oxidative stress through the inhibition of the PI3K/AKT/NF-κB pathway and the regulation of NLRP3-mediated pyroptosis.